AVALIAÇÃO DA DENSIDADE EM TRÊS CULTIVARES DE CANA-DE-AÇÚCAR (SACCHARUM OFFICINARUM L.), SOBRE O CARACTER AFILHAMENTO - Buratti, João V.; Quadros, Valmir J. d.; Abreu, Fernando B.; Silva, José A. G. d.; Batistti, Gabriel (Salão do Conhecimento, 2013)
Resumo